HISTORY OF THE PRESS IN KARAKALPAKSTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides information about the history of the first press and the first newspapers and magazines in Karakalpakstan.Mass media in Uzbekistan is concerned with the situation of Uzbek media. Although a government decree officially eliminated state censorship in 2002, it has continued to severely restrict independent journalism, particularly following the Andijon uprising of 2005. Licensing and regulation are the purview of the State Press Committee and the Inter-Agency Coordination Committee, which use their authority to harass and delay the activities of independent media outlets. In late 2006, authorities further tightened state control by requiring re-registration by all media outlets not passing a summary review of qualifications. In 2005 some 30 to 40 independent television stations and seven independent radio stations were in operation, but four state-owned television stations, run by the Television and Radio Company of Uzbekistan, dominated the market. No live programming is allowed.Total newspaper readership is estimated at only 50,000; the newspaper market is dominated by the state-owned papers Pravda Vostoka, Halq Sozi, and Narodnoye Slovo. The largest privately owned papers are Novosti Uzbekistana, Noviy Vek, Noviy Den, and Mohiyat. The state controls newspaper distribution and materials supply. In the early 2000s, newspaper articles occasionally have criticized government policy and social conditions, but bribery of journalists is common.